THE BYZANTINE REPRESENTATION OF THE ‘ANNOUNCEMENT OF THE NATIVITY OF THE THEOTOKOS’ – UNDERLYING APOCRYPHAL TEXT, PATRISTIC REFLECTIONS, LITURGICAL PERSPECTIVES, THEOLOGICAL HIGHLIGHTS, AND ICONOGRAPHIC PATTERN - SOLOMON, Gabriel Ștefan; PAȘCA-TUȘA, Stelian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
The present study aims first and foremost to provide (ikon) painters with the theological content required to carry out a theoretical process of familiarisation with the basic notions that they would be recommended to take into consideration before starting to work on an ikon. In the absence of this information, a painter would find it difficult to understand the theological message of the event they are rendering in art form and therefore encounter significant hindrances in attaining the final goal of their confession of faith. Furthermore, by highlighting the way the pattern of representation of the ikon/scene has evolved and subsequently crystallised, this paper seeks to enable (ikon) painters to understand the defining elements that lie at the foundation of the Byzantine model for representing an event are, to avoid the exclusion of certain essential details from their renditions, which need to fit into the dynamism of Church Tradition. To that end, we have set out to apply these theoretical rigors to a scene from the life of the Mother of God – the announcement of her birth –to provide the reader with the opportunity to take note of the steps to follow before creating an ikon/scene.